Le développement économique de la Corée du Sud depuis 1950 - Dominique Barjot (Les Cahiers de Framespa)
Since 1998, South Korea reestablished its economic position spectacularly. As the fifteenth economic power in 2010, the country grew rapidly (with +6.1% to GNP in 2010) and is benefiting from a large surplus in its balance of payments. South Korea retains its developmental model created in the 1960s. In spite of the heavy aftermath of the Japanese Occupation and the Korean War, the strategic changes of the 1960s permitted the adoption of a self-sustained growth model from 1972 to 1979. The Korean economy succeeded in face of the changes of the 1980s and the crises of the 1990s, and remained competitive during the 2000s. In terms of competitiveness, South Korea ranked eleventh in the world thanks to its productivity gains, the power of its groups (Samsung, LG, Hyundai, SK), its research and development efforts, and its massive investments in human capital (through universities and centers of research).